Rol y mejores prácticas del equipo líder y su impacto en la innovación de empresas de la Zona Metropolitana de Monterrey - Avila Hernández, Laura Elizabeth; Alarcón Martinez, Gustavo Juan (UANL Facultad de Contaduría Pública y Administración, 2015)
Abstract. This research article elaborates on the leadership or high management teams that have taken into account the innovation challenges within their organizations and the best practices carried out by them. In that token some business innovation definitions are depicted, as well as findings by business researchers on best innovation practices conducted namely by leadership or high management teams. Lastly, the regression analysis results and conclusions are show.